PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT ULTRAJAYA MILK Tbk PERIODE 2013-2022 - Mohammad Sya’ban Abi Putra; Syafrizal (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio on PT Ultrajaya Milk Tbk's Return On Asset, both partially and simultaneously. The independent variables used in this research are Current Ratio and Debt to Equity Ratio, while the dependent variable used in this research is Return On Asset. The research method used in this research is an associative quantitative method. The data collection technique used in this research is secondary data. The sample and population in this research are the financial reports of PT Ultrajaya Milk Tbk for the 2013-2022 period. The data analysis techniques used are descriptive analysis test, classical assumption test, correlation coefficient test, coefficient of determination test, multiple regression analysis test, t test and F test with the SPSS version 22 application. The results of the study show that partially the Current Ratio has no significant effect on Share Price where tcount is 1.631 < ttable 2.36462 with a significant value of 0.147 > 0.05. Partially, the Debt to Equity ratio has no significant effect on share prices, where t is 0.873 < t table 2.36462 with a significant value of 0.412 > 0.05. Simultaneously the Current Ratio and Debt to Equity Ratio do not have a significant effect on Return On Asset, where the Fcount value is 1.332 < Ftable 4.74 with a significant value of 0.324 > 0.05.